2010
DOI: 10.1111/j.1365-2753.2010.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of cost‐effectiveness of varenicline and comparison of cost‐effectiveness of treatments for major smoking‐related morbidities

Abstract: Varenicline appears to be cost-effective from the perspective of both health care payers and employers, because of reduced health care consumption and costs. The cost-effectiveness of varenicline also compares favourably to that of interventions recommended for the treatment and prevention of smoking-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
(55 reference statements)
2
13
0
Order By: Relevance
“…The results of this economic evaluation closely follow the results reported by Wilson et al, comparing varenicline plus counselling to placebo plus counselling in patients with CVD in Spain, Italy, Portugal and Belgium [10], and the more general results comparing varenicline to alternative therapies in various populations, as reported in Zimovetz et al, [9]. As with Wilson et al, [10], the Markov model reported in this paper is based on an adjusted version of the previously published BENESCO model [11], and the extrapolation of outcomes from a single randomized placebo-controlled trial for varenicline plus brief counselling [8].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The results of this economic evaluation closely follow the results reported by Wilson et al, comparing varenicline plus counselling to placebo plus counselling in patients with CVD in Spain, Italy, Portugal and Belgium [10], and the more general results comparing varenicline to alternative therapies in various populations, as reported in Zimovetz et al, [9]. As with Wilson et al, [10], the Markov model reported in this paper is based on an adjusted version of the previously published BENESCO model [11], and the extrapolation of outcomes from a single randomized placebo-controlled trial for varenicline plus brief counselling [8].…”
Section: Discussionsupporting
confidence: 72%
“…From an economic perspective, over 20 studies have previously demonstrated that varenicline is a cost-effective intervention for smoking cessation from both the health care payer and employers perspective, with incremental costeffectiveness ratio's ranging from dominance to 18 582 per Quality Adjusted Life Year (QALY) gained [9]. Recently, a de novo economic evaluation of smoking cessation treatment in patients with CVD in Spain, Portugal, Belgium and Italy extended this evidence base to those with pre-existing conditions and who are at high risk of morbidity and mortality [10].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking cessation programs are the sole area of behavioral research well tested with COPD patients. These RCTs are largely focused on smoking-cessation medications [31][32][33] ]. Reminder calls, education, behavioral support, ongoing monitoring, reduced copayments, and decision aids all succeeded, to varying degrees, in increasing adherence.…”
Section: Interventions To Improve Adherencementioning
confidence: 99%
“…12 The cost per QALY has been estimated to range between £494 (€654; $716) and £3554 for NRT, between £316 and £2212 for bupropion, and between £950 and £1140 for varenicline. [12][13][14] How are they taken and monitored?…”
Section: Bupropionmentioning
confidence: 99%